2017
DOI: 10.4236/as.2017.87048
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Flavonoids in Brazilian Orange Peels and Industrial Orange Juice Processing Wastes

Abstract: The flavonoid content in orange peels of different Brazilian citrus varieties such as bahia, lima, lima-of-persian, morcote, pera, ponkan, seleta, cravo, kinkan and pomelo was assessed. Industry processing juice wastes such as bagasse, bagasse residues, animal feeding bagasse, pulp WEUE and CORE-wash were also analyzed. The HPLC analysis indicates that the most abundant flavonoids found in these Brazilian citrus peels are hesperidin and naringin. The solvents used are selective for flavonoid extraction, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…[21]. Other studies have demonstrated the presence of flavonoids [22,23]. The concentration of total phenolic compounds in kumquat (98.55 ± 1.93 mg GAE•100 g −1 ) was much lower than the F. crassifolia collected in Taiwan, China (229 mg GAE•100 g −1 ) [8].…”
Section: Resultsmentioning
confidence: 78%
“…[21]. Other studies have demonstrated the presence of flavonoids [22,23]. The concentration of total phenolic compounds in kumquat (98.55 ± 1.93 mg GAE•100 g −1 ) was much lower than the F. crassifolia collected in Taiwan, China (229 mg GAE•100 g −1 ) [8].…”
Section: Resultsmentioning
confidence: 78%
“…Compounds such as baicalin, baicalein, naringenin, naringin, eugenol and methyl eugenol can be found in several other higher plants 86 , 91 . In addition, these compounds were also reported to be present in agro-industrial waste of Citrus 92 , 93 and apple pomace 94 , 95 .…”
Section: Challenges and Opportunitiesmentioning
confidence: 96%
“…This is explainable since the most abundant Citrus flavonoid is hesperidin [53]. The orange hesperidin content is 28-42 mg/g of dry peel and 12-44 mg/g of waste from orange juice [54]. It is known that the beneficial effects of flavonoids are due to their anti-oxidant properties, which are a key role in fighting several degenerative diseases.…”
Section: Perspectives Of Flavonoids With Emphases On Hesperidin and Hmentioning
confidence: 99%